P01.069 Re-irradiation for recurrent glioma: outcome evaluation, toxicity and prognostic factors assessment. A multicenter retrospective study by the Brain-Study-Group of the Radiation Oncology Italian Association (AIRO). (19th September 2018) - Navarria, P; Minniti, G; Pinzi, V; Draghini, L; Borzillo, V; Ciammella, P; Scoccianti, S; Amelio, D; Krengli, M; Buglione di Monale, M
Abstract: Background: The role of re-irradiation is still under investigation, particularly regarding to the appropriate patients selection, the time interval between the first and second irradiation, and the optimal RT schedule. The aim of the present study was to evaluate clinical outcome of patients with recurrent glioma underwent re-irradiation in 13 Italian Centers. Material and Methods: Data of 321 recurrent glioma patients underwent re-irradiation were reviewed. The data collection focused on patients, tumor, and treatments characteristics at diagnosis and at recurrence, interval time between diagnosis and local relapse, features of re-irradiation concerning target volume, total doses and fractionations used, acute and late toxicity. Overall survival (OS) was calculated from the date of re-irradiation to the time of death or to the last follow-up examination. Results: Among 321 patients evaluated, 223 had primary diagnosis of glioblastoma, 81 grade III gliomas, 17 low grade glioma. At recurrent time the median age was 53 years (range 20–82 years) and the majority (92%) of patients had a KPS ≥70. Re-irradiation was performed in all 321 patients at a median time of 15 months (range 3–340 months). The median total dose prescribed was 25 Gy in 5 fractions (range 10–52.5Gy in 1–15 fractions). A combined treatment, including surgery and/or chemotherapy was carried out in 102 patients while 219 received radiation therapy only. The median follow up time was 8.2 months (range 2–73 months) for the whole cohort and 17.6 months (range 3–67.7 months) for the alive patients. The median OS time, and the 6, 12, 24 months OS rate were 9.5 months (95%CI 8.2–10.4), 84% (95%CI 80–88), 47% (95%CI41-52), and 22% (95%CI17-27), respectively. At the last observation time 54 are alive and 267 dead. Acute grade 1–2 toxicity was recorded in 43 (13.4%) patients. Grade 1 radionecrosis occurred in 16 patients, grade 2 in 12, and grade 3 in 1. Univariate analysis showed the statistical significance of the extent of surgical resection, histology of primary tumors, IDH and MGMT status at diagnosis; at relapse time age, KPS, the interval between first and second radiation therapy, and the combined treatment performed were recorded as influencing survival. Age, KPS, histology, IDH and MGMT status were confirmed as influencing survival also on multivariate analysis. Conclusion: According to our results, re-irradiation could be considered a safe and feasible therapeutic option for recurrent high grade glioma. Multidisciplinary evaluation is mandatory to assure the best treatment where local therapy is part of multimodal management.